KARAKTERISTIK DINAMIK STRUKTUR ROKET RKN BERTINGKAT PADA KONDISI TERBANG-BEBAS (FREE FLYING) - HPS, Sugiarmadji (Indonesian Journal of Aerospace, 2010)
Dynamic Characteristic Data of a rocket structure, such as eigenvalues and eigenvectors (mode shapes), are needed to protect the payload components’ safety to the 1st frequency resonance of rocket structures. Here, dynamic characteristic data analysis for the RKN Two-Stages rocket structures will be conducted by using a software based on a Finite Element Methods-FEM. On “free-flying” conditions, normal mode analysis results show that the 1st natural frequency of the RKN rocket from the first up to sixth mode shapes are of ω ≤ 5.56895E-4 Hz. It means that payload components are safe tothe 1st natural frequency of the rocket structures. The 1st natural frequency of rocket structures will give influence to the payload components in lateral and vertical directions at higher than = 134 Hz.